PENGARUH SUHU DAN LAMA SIMPAN TERHADAP VIABILITAS POLEN PETUNIA (Petunia Inflata) - Clement Panji; Maria Marina Herawati (Politeknik Negeri Lampung., 2020)
Petunia (P. inflata) is one of the most commonly cultivated ornamental plants because it has different flower sizes, and is easier to grow at various media and temperatures. Indonesia is one of the exporting Countries for Petunia hybrid seed. As one of the countries that provide hybrid seeds, the problem that often faced when making pollination is the availability of pollen with high viability because pollen viability can decrease/disappear within a specified period. The purpose of this research is to determine the effect of temperature and storage period on the viability of Petunia pollen and determine the best temperature and storage period to keep Petunia pollen. The design of this study uses a Randomized Block Design with Split Plot Design. The main plot consists of a storage period for seven days, 14 days, 21 days, and 28 days. The sup plots include storage temperature treatment at room temperature, 5ËšC, -5ËšC, and -15ËšC, there repeated for three times. Data analysis using Analysis of Variant (ANOVA) and further testing using 5% Duncan Multiple Range Test (DMRT). The observed parameter consisted of the germination energy of pollen, pollen tube length, and colored pollen. The results showed that the lower temperatures could keep pollen viability for longer. The longer pollen stored, the viability will decrease further -15Â°C storage temperature can maintain pollen viability high up to 28 days of storage.